The decipherment of linear B - Chadwick, John, 1920-1998 (Cambridge University Press, 1990)
The languages of the ancient world and the mysterious scripts, long undeciphered, in which they were encoded have represented one of the most intriguing problems of classical archaeology in modern times. This celebrated account of the decipherment of Linear B in the 1950s by Michael Ventris was written by his close collaborator in the momentous discovery. In revealing the secrets of Linear B it offers a valuable survey of late Minoan and Myceanean archaeology, uncovering fascinating details of the religion and economic history of an ancient civilisation.
Includes index.
Keywords: Ventris, Michael.; Ventris, Michael; Inscriptions, Linear B.; FOREIGN LANGUAGE STUDY -- Greek (Modern); Inscriptions, Linear B; Linear B; Entzifferung; Electronic books.